Simultaneous green synthesis of Magnetite-Nanoparticles MNPs using microalgae Spirulina sp. for antibacterial activity - Saaduldeen Anwer, Sewgil (Emirates Journal of Food and Agriculture, 2023)
Biosynthesize of Magnetic Nanoparticles MNPs is the environmentally friendly synthesis of nanoparticles that can be used as an alternative to commercially available antibiotics. The present study aimed to determine the ability of biosynthesized magnetic nanoparticles of Spirulina sp. for antibacterial activity. Microalgae isolated from the Gomaspan river cultured on BG11 medium and, is identified using morphology and molecular method and the optimum growth rate of microalgae studied, the biomass used to synthesize of MNPs then was characterized by a visible color change and Scanning electron microscope SEM, FTIR with XRD. Antimicrobial activity of Spirulina sp. and biosynthesize of MNPs. studied using different extracts (ethanol, methanol and Diethyl ether) against growth of Salmonella Typhi, Streptococcus pyogenes, Escherichia coli and pseudomonas aerogenes by disc diffusion and Minimum inhibitory concentration methods. The antibacterial activity from microalgae Spirulina sp. and biosynthesized MNPs from Spirulina sp. showed to inhibit growth of bacteria with both methods and the higher inhibition zone showed as (30-37mm). The minimum inhibition concentration showed with ethanol extract (125-500 µg/l). The current study is first report an eco-friendly and convenient method for the synthesis of MNPs using Microalgae Spirulina sp. extracts. This biosynthetic process might be useful pharmaceuticals, and medicine treatment of pathogenic bacteria. Keywords: Nanoparticle, Magnetic, Spirulina, Antibacterial, solvent extract